Emerging rules for subunit-based, multiantigenic, multistage chemically synthesized vaccines (2008)
(Figure Presented) Seventeen million people die of transmittable diseases and 2/3 of the world's population suffer them annually. Malaria, tuberculosis, AIDS, hepatitis, and reemerging and new diseases are a great threat to human-kind. A logical and rational approach for vaccine development is thus desperately needed. Protein chemistry provides the best tools for tackling these problems. The tremendous complexity of microbes, the different pathways they use for invading host cells, and the immune responses they induce can only be resolved by using the minimum subunit-based (chemically produced ?20-mer peptides), multiantigenic (most proteins involved in invasion), multistage (different invasion mechanisms) vaccine development approach. The most lethal form of malaria caused by Plasmodium falciparum (killing 3 million and affecting 500 million people worldwide annually) was used as target disease since many of its proteins, its invasion pathways, and its genome have been described recently. A New World primate (the Aotus monkey) is highly susceptibly to human malaria; its immune system molecules are 80-100% identical to those of its human counterpart, making it an excellent model for vaccine development. Chemically synthesized ?20-mer peptides, covering all the P. falciparum malaria proteins involved in red blood cell (RBC) invasion were synthesized by the classical t-Boc technology (based on synthetic SPf66 antimalarial vaccine information for identifying targets) and assayed in a highly sensitive, specific, and robust test for detecting receptor-ligand interactions between high-activity binding peptides (HABPs) and RBCs. HABPs were identified, some in which the molecule displays genetic variability (to be discarded due to their tremendous complexity) and elicits a strain-specific immune response and others that are conserved (no amino acid sequence variation). Conserved HABPs were synthesized in a polymeric form by adding cysteines at their N- and C-terminal ends to be used for monkey immunization. They became nonimmunogenic (no antibodies were induced) nonprotection inducers (monkeys were not protected against P. falciparum malaria challenge with a highly infective strain) suggesting a code of immunological silence or nonresponsiveness for these conserved HABPs. A large number of monkey trials involving a considerable number of Aotus monkeys were performed to break this code of immunological silence by replacing critical residues (determined by glycine peptide analogue scanning) to find that the following amino acid changes had to be made to render them antibody and protection inducing: F?R; W?Y; L?H; I?N; M?K; P?D; Q?E; C?T. The three-dimensional (3D) structure of and gt;100 of these native modified HABPs (determined by 1H NMR) revealed that the following structural changes had all to be achieved to allow a better fit into the major histocompatibility complex class II (MHC II)-peptide-TCR complex to properly activate the immune system: ?-helix shortening, modifying their ?-turn, adopting segmental ?-helix configuration, changing residue orientation, and increasing the distance of those residues fitting into the MHC II molecules from antigen-presenting cells. More than 100 such highly immunogenic, protection-inducing (against P. falciparum malaria) modified HABPs have been identified to date with this methodology, showing that it could lead to developing a highly effective subunit-based, multiantigenic, multistage synthetic vaccine against diseases scourging humankind, malaria being one of them. © 2008 American Chemical Society.